Analisis Tingkat Kognitif Soal pada Buku Kemdikbudristek 2022 Materi Teorema Pythagoras - Simarmata, Gayus; Simanungkalit, Rich Hunter; Sinabang, Febrianto Samuel (PendIPA Journal of Science Education, 2024)
The purpose of this study was to determine the distribution of cognitive levels of practice questions and competency test questions on the Pythagorean Theorem material in the Electronic School Book (BSE) for Mathematics for Junior High Schools/Islamic Junior High Schools Class VIII published by the Ministry of Education, Culture, Research and Technology in 2022 based on the Revised Bloom's Taxonomy. The revised Bloom's Taxonomy used is in the cognitive process consisting of: C1-remembering, C2-understanding, C3-applying, for Low Order Thinking Skill (LOTS), C4-analyzing, C5-evaluating, and C6-creating for High Order Thinking Skill (HOTS). This type of research is descriptive research. The data sources taken in this study were practice questions and competency test questions. The practice questions analyzed amounted to 40 questions out of 20 questions, and the competency test questions analyzed amounted to 14 questions out of 10 questions. Based on the results of the analysis for practice questions, it contains 80% LOTS questions, namely C2 questions 30% and C3 questions 50%. HOTS questions 20%, namely question C4. Questions of cognitive levels C1, C5, and C6 were not found. For Competency Test questions, it contains 85.72% LOTS questions, namely question C2 50.00% and question C3 35.72%. HOTS questions 14.28%, question C4 7.14%, question C6 7.14%. Questions C1 and C5 were not found.